Identifikasi Bunga Normal dan Abnormal Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) Pada Kebun Binaan PPKS di Kabupaten Dharmasraya - Narti Sutia; Irfan Suliansyah; Ade Noferta (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2018)
The objective of the research is to identify normal and abnormal flowers on oil palm clones from tissue culture in PPKS plantation in Dharmasraya District. This research used descriptive method and the data were taken by purposive sampling. Forms of normal and abnormal flowers were described, as well as the stages of flowers development. Result indicated that normal female flowers have 3 stigmas and 3 lobes, while abnormal female flowers have more than 3 stigmas and 3 to 7 lobes. In comparison, normal female flowers have 6 circles of corollas while abnormal female flowers have 7 circles with additional carpels on corolla. There are three kinds of abnormalities found i.e.: transvestite coat, heavy coat, and very heavy coat (abort). The percentages of normal flowers is 80% while the abnormal flowers is 20%.